Exchange rate pass-through to domestic inflation in a pricing model incorporating distribution chain structure - Jia Ji (Journal of Applied Economics, 2022)
This study investigates the pass-through of exchange rate shocks to different aggregate prices in China. The baseline analysis is carried out with vector autoregressive models incorporating a distribution chain of pricing, and various modifications are examined for robustness. The central results show an appreciation of the local currency tends to suppress domestic inflation at the early production stages, although the pass-through effect only amounts to a moderate degree for consumer prices. As the contribution of external factors to the persistently low inflation environment mostly has been modest, the paper suggests that the monetary authority can contribute to the permanent component of low exchange rate pass-through to domestic inflation, by continually conducting a credible and efficient stable-inflation policy.
Keywords: 330; distribution chain; Exchange rate pass-through; inflation; policy design